Participation and poverty reduction: issues, theory, and new evidence from South Africa - Hoddinott, John F.; Haddad, Lawrence J.; Besley, Timothy; Adato, Michelle (International Food Policy Research Institute, 2001)
This paper examines the relationship between community participation and the efficacy of interventions designed to reduce poverty. We develop some simple analytics that are used to structure a review of the extant literature and motivate the analysis of the impact of participation on the efficacy of public works interventions in South Africa.